Differential heat and entropy of adsorption of methanethiol in sodalite - Abdullaxanova, Gulrukh; Ergashev, Oybek (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article presents experimentally obtained values of the differential enthalpy of methane thiol (methanethiol) adsorption in sodalite at a temperature of 303 K. The enthalpy values were measured using a Tian-Calvet type DAC-1-1A microcalorimeter connected to a universal high-vacuum system. Based on equilibrium pressure values, the differential values of free energy (Gibbs energy) were calculated. Using the experimentally measured differential heat and Gibbs energy values, the change in adsorption entropy and its average value were theoretically estimated using the Gibbs–Helmholtz equation. A regular correlation between the amount of methanethiol adsorbed on sodalite and the changes in differential enthalpy and entropy was demonstrated. Furthermore, the mechanism of adsorption was determined—from the initial adsorption region to the region corresponding to the condensation heat of methanethiol—as well as the law governing the filling of the zeolite pore volume by methanethiol molecules. The regular variation of differential enthalpy values with the amount of Na+ cations in the zeolite structure indicated that methanethiol molecules form sequential mono- and dimeric ion-molecular complexes of the type 2CH3SH:Na+ with sodium cations. The average entropy change was found to be -37 J/mol·K, indicating that the mobility of methanethiol molecules was significantly restricted.